Effects of aerobic exercise in addition to core stabilization exercises on functional capacity, physical performance and fall risk in geriatric individuals with chronic non-specific low back pain - Şafak Kuzu; Mehmet Canli; İrem Valamur; Anıl Özüdoğru; Halil Alkan; Abdulmetin Hartavi (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background Geriatric individuals may frequently develop low back pain after physiological changes. The aim of our study was to compare the effects of core stabilization exercises alone and aerobic exercises in addition to core stabilization exercises on functional capacity, physical performance and fall risk in geriatric individuals with chronic non-specific low back pain (CNLBP). Methods In this randomized controlled study, 30 participants in the core stabilization exercise group (CG) received intervention, and the mean age of this group was 70.43 ± 4.48 years. The mean age of the 30 participants in the core stabilization + aerobic exercise group (CAG) was determined as 69.60 ± 4.05 years. Sixty individuals with CNLBP were included in the study and divided into two groups: CG (n = 30) and CAG (n = 30). CG received core stabilization exercises for 8 weeks, while CAG received aerobic exercise using a treadmill in addition to core stabilization exercises for 8 weeks. Functional capacity (six-minute walk test), physical performance (Oswestry Disability Index), fall risk (Biodex Balance System), pain intensity (Visual Analogue Scale), depression status (Beck Depression Inventory) and kinesiophobia level (Tampa Kinesiophobia Scale) were evaluated before and after the treatment programmes. Results Significant improvements were found in all parameters in both groups after the treatment programmes (p < 0.05). In addition, functional capacity, physical performance, fall risk, pain severity and depression scores improved more in CAG compared to CG (p < 0.05), but the improvement in kinesiophobia was similar (p > 0.05). Conclusions The results of the study showed that both core stabilization exercises alone and core stabilization exercises combined with aerobic exercise led to improvements in patients with CNLBP. However, the group that combined aerobic and core stabilization exercises (CAG) showed greater improvements, particularly in functional capacity, physical performance, fall risk, pain intensity, and depression levels. These findings suggest that core stabilization exercises are beneficial for CNLBP, but adding aerobic exercise may enhance these positive effects. Therefore, incorporating aerobic exercise into rehabilitation programmes for older adults with CNLBP may provide additional clinical benefits. Trial registration This clinical trial was registered at http://clinicaltrials.gov (Number: NCT06946758; registration date: 21/04/2025).